In vitro multiplication of wild Manihot species with different naphthaleneacetic acid and benzylaminopurine concentrations (Acta Scientiarum. Biological Sciences, 2021)
In vitro multiplication is an important tissue culture technique that is capable of efficiently producing seedlings at any scale. It is a propagation method based on the aseptic culture of small propagules in a suitable culture medium to enable plant regeneration. Multiplication experiments conducted in vitro to set protocols adapted to wild Manihot species have used modified mineral salts and MS vitamins as basic culture medium. Here, 25 treatments based on combinations of the regulators benzylaminopurine (BAP) and naphthaleneacetic acid (NAA) at 0, 0.025, 0.05, 0.075, and 0.1 mg L-1 were used for in vitro multiplication of three genotypes of wild Manihot species (M. violaceae Pohl Müll. Arg., M. pseudoglaziovii Pax & Hoff., and M. flabellifolia Pohl). Plant height and the number of 1 cm minicuttings, number of roots, shoots, green leaves and senescent leaves were recorded 120 days after explant inoculation. M. violaceae Pohl. Müll. Arg. and M. flabellifolia Pohl. presented favorable results with 0.05 and 0.025 mg L-1 NAA, respectively. Culture medium lacking NAA and BAP favored the in vitro growth of M. pseudoglaziovii Pax & Hoff.